Extracorporeal Shock Wave Therapy with Low-Energy Flux Density Treatment Applied to Hemiplegia Patients on Somatosensory Functions and Spatiotemporal Parameters - Deniz, Gulnihal; Bilek, Furkan; Gulkesen, Arif; Cakir, Murteza (Ataturk Univ, 2024)
Background: We aimed to investigate the effect of Extracorporeal Shock Wave Therapy (ESWT) applied to patients with hemiplegia on somatosensory data, spatiotemporal parameters, posture, and muscle tone. Methods: This was a double-blind, randomised, controlled trial. Patients were randomised within pairs to either the experimental (ESWT) group (n = 20) or the control group (n = 20). All patients participated in the same conventional stroke rehabilitation program for 60 minutes of treatment a day, 5 times a week for 6 weeks (30 sessions). Patients assigned to the ESWT group received additional ESWT over the plantar fascia 3 days/week for 6 weeks. Timed Up and Go (TUG) test, Modified Ashworth Scale (MAS) score, Posture Assessment Scale for Stroke Patients (PASS), spatiotemporal parameters, Semmes-Weinstein monofilament (SWM) test, and vibration sensation test (VST) were performed in all participant before and after treatment. Results: In the ESWT and control groups, statistically, significant differences were obtained in the posttreatment analysis than pre-treatment. Significant differences were found in foot angle, step cycle duration, swing phase, cadence, gait cycle distance, and VST values after ESWT treatment (P < .01). Conclusion: When combined with a neurological rehabilitation program, it was determined that ESWT applied to the plantar face of the foot in individuals with hemiplegia increased somatosensory functions and was more successful in developing postural control and balance.
Keywords: Hemiplegia; spatiotemporal parameters; somatosensory; balance; spasticity; ESWT